NETWORK-BASED COMPUTER BY USING THE SOUNDCARD PACKET RADIO MODEM - Muhamad Ridwan; Jalinas Jalinas, SKom, MM (Jurnal Sistem Komputer, 2000)
Network-based computer by using the soundcard packet radio modem has many features compared to conventional networks, packet radio networks can use the soundcard as a radio modem, thus reducing costs in their manufacture, and soundcards that we use for the radio modem can we change the configuration so that it can reduce costs in the production network packet radio.